RISK FACTORS FOR THE ANEMIA IN PREGNANT WOMEN: A LITERATURE REVIEW - Nurnaningsih Nurnaningsih; Mardiana Ahmad; Isharyah Sunarno; Nur Aliya Arsyad (Nurse and Health: Jurnal Keperawatan, 2022)
Background: Anemia in pregnancy is still a global public health problem and is the largest contributor to morbidity and mortality. Some studies report that risk factors for anemia vary from place to place, so more in-person observations are needed regarding anemia risk factors. Objectives: This study aimed to determine the risk factors of anemia in pregnant women. Methods of using literature review studies. Design: This study design is a literature review to search and review article from database and the theory which is descriptive. Data Sources: Search for scientific articles using the Mendeley application by entering the keyword "Risk Factors, Anemia, Pregnancy" with Published year 2018-2021, English and Indonesian, full text, National journal has ISSN and open access. Review Methods: The literature review method using narrative review based on inclusion criteria, namely articles discussing anemia in pregnant women, published in 20158-202, International and National Publications, having ISSN National Journals, Articles using English, original articles, full text and open access. While the Exception Criteria for Articles other than English, type of research literature review and RCT, articles are then collected and a journal summary is made containing the name of the researcher, the year the journal was published, the title of the study, the method and a summary of the results or findings. The summary of research journals is entered into a table according to the format, and 10 articles are eligible. Results: From the 10 selected articles, it can be concluded that the risk factors for anemia, especially in developing countries, are multifactorial, including micro-iron deficiency, folate, and vitamins A and B12 as well as anemia due to parasitic infections such as malaria and hookworms or chronic infections such as TB, HIV, parasites. intestines, infection of working mothers (farmers), contaminated drinking water sources, consumption of coffee/tea and diet. Meanwhile, other factors in Indonesia are unfavorable geographical location, level of education, lack of public awareness of health, socio-economic situation, parity (number of children), and chronic energy shortages (KEK). Conclusion: Anemia is still a global health problem and still has to be addressed, especially in developing countries. Therefore, efforts are needed to better understand the main causes of anemia, including iron deficiency as well as other nutritional deficiencies, diseases, and Hb disorders related to anemia so that appropriate action can be given. Biochemical measurement of micronutrients (especially iron and Vitamin A), inflammatory signs in addition to hematological index when assessing anemia clinically are also urgently needed.